In-vivo characterization of macro- and microstructural injury of the subventricular zone in relapsing-remitting and progressive multiple sclerosis - Cellerino, Maria; Schiavi, Simona; Lapucci, Caterina; Sbragia, Elvira; Boffa, Giacomo; Rolla-Bigliani, Claudia; Tonelli, Serena; Boccia, Daniele; Bruschi, Nicolò; Tazza, Francesco; Franciotta, Diego; Inglese, Matilde (Frontiers in Neuroscience, 2023)
Introduction The subventricular zone (SVZ) represents one of the main adult brain neurogenesis niche. In-vivo imaging of SVZ is very challenging and little is known about MRI correlates of SVZ macro- and micro-structural injury in multiple sclerosis (MS) patients. Methods The aim of the present study is to evaluate differences in terms of volume and microstructural changes [as assessed with the novel Spherical Mean Technique (SMT) model, evaluating: Neurite Signal fraction (INTRA); Extra-neurite transverse (EXTRATRANS) and mean diffusivity (EXTRAMD)] in SVZ between relapsing-remitting (RR) or progressive (P) MS patients and healthy controls (HC). We are also going to explore whether SVZ microstructural injury correlate with caudate (a nucleus that is in the vicinity of the SVZ) or thalamus (another well-defined grey matter area which is further from SVZ than caudate) volume and clinical disability. Clinical and brain MRI data were prospectively acquired from 20 HC, 101 RRMS, and 50 PMS patients. Structural and diffusion metrics inside the global SVZ, normal appearing (NA-) SVZ, caudate and thalamus were collected. Results We found a statistically significant difference between groups in terms of NA-SVZ EXTRAMD (PMS>RRMS>HC; p = 0.002), EXTRATRANS (PMS>RRMS>HC; p<0.0001), and INTRA (HC>RRMS>PMS; p = 0.009). Multivariable models showed that NA-SVZ metrics significantly predicted caudate (R2 = 0.21, p < 0.0001), but not thalamus, atrophy. A statistically significant correlation between EXTRAMD and EXTRATRANS of the NA-SVZ and EDSS (r=0.25, p=0.003 and r=0.24, p = 0.003, respectively) was found. These findings were confirmed in analyses restricted to RRMS, but not to PMS patients. Discussion In conclusion, the microstructural damage we observed within the NA-SVZ of MS patients – reflecting higher free water content (higher EXTRAMD), cytoarchitecture disruption and astrogliosis (higher EXTRATRANS and lower INTRA) - was more evident in the progressive as compared to the relapsing phases of MS. These abnormalities were significantly associated with a more pronounced caudate atrophy and higher clinical disability scores. Our findings may support the neuroprotective role of SVZ in MS patients.